2019
DOI: 10.1074/jbc.ra119.011518
|View full text |Cite
|
Sign up to set email alerts
|

The terminal sialic acid of stage-specific embryonic antigen-4 has a crucial role in binding to a cancer-targeting antibody

Abstract: Cancer remains a leading cause of morbidity and mortality worldwide, requiring ongoing development of targeted therapeutics such as monoclonal antibodies. Carbohydrates on embryonic cells are often highly expressed in cancer and are therefore attractive targets for antibodies. Stage-specific embryonic antigen-4 (SSEA-4) is one such glycolipid target expressed in many cancers, including breast and ovarian carcinomas. Here, we defined the structural basis for recognition of SSEA-4 by a novel monospecific chimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Antibodies against several GSLs, designated as stage‐specific embryonic antigens (SSEAs), have been widely used to characterize the GSL profiles of embryonic stem cells (ESCs). Since these antibodies often display cross‐reactivities [4], GSL profiles in human ESCs and differentiated derivatives are more accurately delineated by systematic survey using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI TOF MS) and tandem mass spectrometry analyses. We previously reported that during differentiation of ESC to embryoid body, the core structures of GSLs switched from globo‐ and lacto‐ to ganglio‐series [5].…”
mentioning
confidence: 99%
“…Antibodies against several GSLs, designated as stage‐specific embryonic antigens (SSEAs), have been widely used to characterize the GSL profiles of embryonic stem cells (ESCs). Since these antibodies often display cross‐reactivities [4], GSL profiles in human ESCs and differentiated derivatives are more accurately delineated by systematic survey using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI TOF MS) and tandem mass spectrometry analyses. We previously reported that during differentiation of ESC to embryoid body, the core structures of GSLs switched from globo‐ and lacto‐ to ganglio‐series [5].…”
mentioning
confidence: 99%
“…The glycolipid stage‐specific embryonic antigen‐4 (SSEA‐4) is stabilized by its terminal sialic acid and is present in the OC cell lines and breast cancer cell lines. Soliman et al found that mouse‐human chimeric antibody ch28/11 recognizes this sialic acid of SSEA‐4, representing a promising therapeutic avenue for targeting OC 41 …”
Section: Resultsmentioning
confidence: 99%
“…Soliman et al found that mouse‐human chimeric antibody ch28/11 recognizes this sialic acid of SSEA‐4, representing a promising therapeutic avenue for targeting OC. 41 …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, SSEA-4 has been suggested to be a novel therapeutic target in a variety of malignancies (42)(43)(44). For example, a mAb directed against SSEA-4 (MC-813-70) has been suggested as a potential therapeutic agent for triplenegative breast cancer cells expressing SSEA-4 (43).…”
Section: Discussionmentioning
confidence: 99%